Pengaruh Penyerapan β-Karoten pada CPO dengan Variasi Perbandingan antara Pasir Kuarsa dengan Biochar Cangkang Kelapa Sawit sebagai Adsorben - Ari Auditia Jurlian Pratama; Rafael Remit Winardi (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2026)
Crude Palm Oil (CPO) contains β-carotene, a natural pigment that gives it a yellowish-red color and serves as an indicator of palm oil quality. This study aims to determine the effect of varying ratios of quartz sand and oil palm shell biochar as adsorbents on β-carotene content and CPO quality. The adsorbents were prepared through a melting process using a furnace, then activated with a 1 M NaOH solution and applied to CPO using the column method. The parameters observed included β-carotene content, Deterioration of Bleachability Index (DOBI), free fatty acid (FFA) content, and moisture content. The data were analyzed using normality and homogeneity tests, One-Way Analysis of Variance (ANOVA), followed by Duncan’s Multiple Range Test (DMRT) at a significance level of 5%. The results showed that variations in the ratio of quartz sand to oil palm shell biochar had a significant effect on the DOBI value (p=0.007), β-carotene content (p<0.001), and FFA content (p=0.003), while they had no significant effect on moisture content (p=0.512). Treatment P3 produced the best β-carotene adsorption capacity with a β-carotene concentration of 385,500 ppm and the lowest ALB content of 3.4867%, while P1 had the highest DOBI value of 2.420. Thus, the combination of quartz sand and oil palm shell biochar has the potential to be used as an alternative adsorbent to improve CPO quality by reducing β-carotene content without significantly affecting moisture content.